Bulgaria : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in Bulgaria during 1990-95. In 1993, GDP continued to contract, albeit more slowly than previously. Real GDP declined by 2.4 percent owing to a drought-induced collapse in agricultural output. As consumption-driven imports rose and exports fell, the lower real GDP in 1993 was accompanied by a large current account deficit. The adoption of restrictive fiscal and incomes policies in 1994 enabled Bulgaria to retain the gains in external competitiveness acquired from the nominal depreciation.